2022
DOI: 10.3390/su142113849
|View full text |Cite
|
Sign up to set email alerts
|

Architects’ Perceptions about Sustainable Design Practice and the Support Provided for This by Digital Tools: A Study in Australia

Abstract: The fundamental goal of sustainable design for the built environment is to optimise the performance of buildings to minimise their impact on the environment. To achieve this goal, contemporary architects use a range of digital design environments, such as Computer-aided Design (CAD) or Building Information Modelling (BIM) tools. These allow architects to implement sustainable design principles and make optimal decisions about the ecological and energy properties of the building or environment being designed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Interestingly, our study found that 81% of participants perceive sustainable interior design practices as more than just passing trends. This perception mirrors the findings of Yu et al [47], who discovered a similar sentiment among architects regarding sustainable architecture. It is encouraging to see that professionals in the built environment increasingly view sustainability as a fundamental and enduring aspect of their practice.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, our study found that 81% of participants perceive sustainable interior design practices as more than just passing trends. This perception mirrors the findings of Yu et al [47], who discovered a similar sentiment among architects regarding sustainable architecture. It is encouraging to see that professionals in the built environment increasingly view sustainability as a fundamental and enduring aspect of their practice.…”
Section: Discussionsupporting
confidence: 89%
“…A comprehensive understanding of the subject will help designers and consultants implement and improve their sustainable design practices and offer new information to software developers about the needs of the industry for more effective development of sustainable design tools [76]. To effectively support these activities, it is crucial to match these understandings with the potential and preparedness of digital technologies.…”
Section: Existing Obstacles To the Application Of Sustainability To U...mentioning
confidence: 99%
“…Furthermore, the institutional level of preparedness in the launching, awarding, and monitoring of urban bridges plays a valuable role. Digital technologies play a significant part in the development of a more effective and responsible infrastructure to fulfill social, environmental, and economic needs, and techniques have evolved to become an innovative force throughout the lifespan of modern AEC projects [76].…”
Section: Existing Obstacles To the Application Of Sustainability To U...mentioning
confidence: 99%
“…Concrete and cement production, responsible for 8% of all industrial GHG emissions, are among the most recorded heavy wastesaccounting for 15-28% of all solid waste (Hu et al, 2021;Zhang et al, 2023). As such, within the architecture, engineering and construction (AEC) industry, a fundamental shift is required for addressing these negative impacts, with an emphasis on reducing concrete mining, GHG emissions and waste generation, at both material and production workflow levels (Yu et al, 2022). One promising approach that addresses such urgencies is biodesign, a field that proposes integrating processes of living organisms into design workflows, where materials inherit new biological properties (such as carbon fixation and lower ecological footprint), in addition to decreasing the amount of energy used (Myers, 2012;Achal and Mukherjee, 2015;Dade-Robertson, 2020;Qiu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%